Polyphenol-rich curry made with mixed spices and vegetables benefits glucose homeostasis in Chinese males (Polyspice Study): a dose-response randomized controlled crossover trial - Haldar S. (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2020)
10.1007/s00394-017-1594-9